Association of changes in lipids with risk of myocardial infarction among people without lipid-lowering therapy. (May 2020) - Tian, Xue; Zuo, Yingting; Chen, Shuohua; Li, Haibin; He, Yan; Zhang, Licheng; An, Ji; Wu, Shouling; Luo, Yanxia; Wang, Anxin
Abstract: Background and aims: Although serum lipids are widely accepted as independent predictors of myocardial infarction (MI), there is insufficient evidence for associations of changes in lipid levels with MI. The present study aimed at investigating the associations between changes in lipids and incidence of MI in people without lipid-lowering therapy. Methods: 64, 031 Chinese participants (mean age: 53.42 ± 11.95 years) without previous MI were enrolled in the study. The participants were divided into four categories based on quartiles of lipid changes. Multivariable Cox regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for MI. Results: During a median follow-up of 7.03 years, 599 individuals developed MI. After adjustment for covariates, increased total cholesterol (TC), increased low-density lipoprotein cholesterol (LDL-C), increased non-high-density lipoprotein cholesterol (non-HDL-C), and decreased high-density lipoprotein cholesterol (HDL-C) were associated with elevated risk of MI, with HRs (95% CIs) in the highest quartile group compared with the lowest quartile group of 1.56 (1.21–2.01), 1.96 (1.49–2.57), 1.95 (1.52–2.50), and 0.69 (0.53–0.90), respectively. However, changes in triglyceride (TG) were not associated with MI risk ( p = 0.8030). Conclusions: Changes in levels of TC, LDL-C, non-HDL-C, and HDL-C, but not TG, were associated with risk of MI. Early detection and control of lipid levels may be beneficial and necessary for young people and those with healthy lipid levels at baseline. Graphical abstract: Image 1 Highlights: Changes in lipids would increase the predictive value of conventional risk factors. Changes in lipids except triglyceride are related to myocardial infarction risk. Early detection and control of lipids is also beneficial for young people.